Morphological Changes of Human Dentin after Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) and Carbon Dioxide (CO(2)) Laser Irradiation and Acid-etch Technique: An Scanning Electron Microscopic (SEM) Evaluation - Shahabi, Sima (J Lasers Med Sci, 2013)
Introduction: The aim of this study was to investigate the morphological changes of human dentin after Erbium-Doped Yttrium Aluminum Garnet (Er:YAG), Carbon Dioxide(CO(2)) laser-irradiation and acid-etching by means of scanning electron microscopic (SEM) Methods: 9 extracted human third molars were used in this study. The teeth were divided in three groups: first group, CO(2) laser with power of 1.5 w and frequency of 80 Hz; second group, Er:YAG laser with output power of 1.5 W frequency of 10 Hz, very short pulse with water and air spray was applied; and third group, samples were prepared by acid-etching 37% for 15 sec and rinsed with air-water spray for 20 sec. Then, the samples were prepared for SEM examination. Results: Melting and cracks can be observed in CO(2) laser but in Er:YAG laser cleanedablated surfaces and exposed dentinal tubules, without smear layer was seen. Conclusion: It can be concluded that Er:YAG laser can be an alternative technique for surface treatment and can be considered as safe as the conventional methods. But CO(2) laser has some thermal side effects which make this device unsuitable for this purpose.